Isolation and Purification of Chickpea (Cicer arietinum) Seeds Protein, Testing Their Antibacterial Activity, and Using to Extend The Shelf Life of Beef Patties - Mohammed A. Alsoufi; Raghad A. Aziz (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2023)
Antimicrobial proteins (AMP) from chickpea (Cicer arietinum L.) seeds were isolated and purified using the saturation of (NH4)2So4 by 80% and gel filtration through Sephacryl S-200, the inhibition zone of the separated peak was 24, and 22 mm for growth of Escherichia coli and Salmonella typhimurium respectively. The molecular mass was 28385 Da estimated through Sephacryl S-200. The optimum pH for activity was 5.5. It was stable at 4.5-7.5, while it lost 21.07 and 55.65% from its activity at pH  3 and 8 respectively, the optimum temperature for activity was 35°C and it was stable at 35°C for 60 min, while it lost all inhibitory activity at 65°C for the same time. The use of AMP at 100 mg resulted in an inhibition zone of 37± 2.92, 35±1.68, 32±2.33, and 33±2.09 mm, with a significant difference at (P≤0.05) against E. coli and S. Typhimurium, Staphylococcus aureus, and Bacillus cereus, respectively. The use of AMP to extend the shelf life of beef patties at 100 mg.kg-1 resulted in a decrease in the total count of bacteria, as it reached 7.4×102±0.18, 4.6×102±0.22 and 2.8×102±0.19 CFU.g-1, while it was 7.4×102±0.23, 8.2×102±0.31, and 9.5×102±0.27 CFU.g-1 in the control sample during a storage period of 0, 3, and 6 d at 4°C. It was observed that there was no significant difference in the control treatment and AMP added on 0 d, while a significant difference was observed at (P≤0.05) for treatments at a storage period of 3 and 6 d at 4°C.